Influence of environmental factors on retention of extensive green roofs with different substrate composition - Baryła, Anna; Karczmarczyk, Agnieszka; Bus, Agnieszka; Hewelke, Edyta (E3S web of conferences, 2019)
Increasing recognition is being given to the adaption of green roofs in urban areas to enhance the local ecosystem. Green roofs may bring several benefits to urban areas including flood mitigation Analysis of environmental factors affecting the outflow of green roofs is the subject of many studies. The work assessed how environmental factors moisture of structural layers and antecedent dry weather period influence the retention on two types of green roof substrates. The monitoring of environmental factors and amount of runoff was carried out on two models of green roofs covered by extensive vegetation (mosssedum-herbs) with substrates of an organic-mineral and mineral composition for 8 months. A statistical regression approach identified potential antecedent meteorological factors and moisture indicators of extensive green-roof retention. Continuous field monitoring data revealed the combined effects of rainfall depth and antecedent dry weather period to explain the measured stormwater retention under a moderate climate conditions regime. It is important to incorporate site-specific planning and assessment prior to green infrastructure design.